Zooplankton community response to eddy during dinoflagellate Noctiluca scintillans blooms off Pakistan, northern Arabian Sea - Dedo, Mahugnon Boris; Lian, Xiping; Li, Kaizhi; Xiang, Chenhui; Tan, Yehui (Journal of oceanology and limnology, 2024)
Eddies are major elements of ocean dynamics that affect ocean production. Understanding their effects on plankton distribution may help understand the dynamics of harmful phytoplankton blooms. Previous studies on the effects of eddies in the northern Arabian Sea have primarily focused on the zooplankton community, and few have observed zooplankton dynamics during winter blooms of Noctiluca scintillans . We investigated zooplankton community structure and the related environmental variability during a N. scintillans bloom that was affected by an eddy in February 2018. The sampling stations were deployed at eddy core and eddy edge distinguished in salinity, temperature, and velocity. Results show that N. scintillans bloomed at the eddy core with high-velocity currents induced by warm eddies that moved from eddy core to eddy edge. As a result, blooms significantly changed the zooplankton community structure. Non-bloom stations had higher zooplankton diversity than bloom stations. Zooplankton at non-bloom stations were dominated by either tunicates or copepods, such as Thalia democratica and Pleuromamma gracilis . In addition to the influence of N. scintillans blooms, the velocity of eddy currents was a crucial factor on the similarities in the zooplankton community composition between eddy edge and eddy core. Moreover, the lower abiotic factors in bloom area contribute to the structuring of the zooplankton community during N. scintillans blooms.